Irish identities sociolinguistic perspectives - Moreno, Carolina P. Amador; Hickey, Raymond, 1954- (Language and social life (Mouton de Gruyter) ;, 2020)
This volume examines in-depth the many facets of language and identity in the complex linguistic landscape of Ireland. The role of the heritage language Irish is scrutinized as are the manifold varieties of English spoken in regions of the island determined by both geography and social contexts. Language as a vehicle of national and cultural identity is center-stage as is the representation of identity in various media types and text genres. In addition, the volume examines the self-image of the Irish as reflected in various self-portrayals and references, e.g. in humorous texts. Identity as an aspect of both public and private life in contemporary Ireland, and its role in the gender interface, is examined closely in several chapters. This collection is aimed at both scholars and students interested in langage and identity in the milti-layered situation of Ireland, both historically and at present. By addressing general issues surrounding the dynamic and vibrant research area of identity it reaches out to readers beyond Ireland who are concerned with the pivotal role this factor plays in present-day societies.